Pneumomediastinum, Pneumoretroperitoneum, Pneumoperitoneum and Subcutaneous Emphysema Secondary to a Penetrating Anal Injury - Yu-Ting Hsiao; Shyh-Wen Lin; Pei Wen Chuang; Ming-Jen Tsai (Diagnostics, 2021)
Simultaneous occurrence of pneumoperitoneum, pneumoretroperitoneum, pneumomediastinum and subcutaneous emphysema is rare. The most reported mechanisms are barotrauma, thermal injury and instrument puncture caused by colonoscopy. Ectopic air may travel into different body compartments through distinct anatomical fascial planes. Definite curative treatment involves surgical repair of the bowel wall defect. Conservative treatment is available in selected patients. Here, we present a case of traumatic penetrating rectal injury leading to developing air in the peritoneum, retroperitoneum, mediastinum, and subcutaneous space with good recovery under conservative treatment.